2020
DOI: 10.1111/jnu.12572
|View full text |Cite
|
Sign up to set email alerts
|

Association of Use of Contract Nurses With Hospitalized Patient Pressure Injuries and Falls

Abstract: Background Hospital‐acquired pressure injuries (HAPIs) and falls are outcomes sensitive to quality of nursing care. Use of contract (traveler) nurses varies among organizations, but there is little research on the effect of contract nurses on nurse‐sensitive outcomes. Objectives To explore the relationship between use of contract nurses and two key nurse‐sensitive outcomes, HAPIs and falls. Research Design This was a cross‐sectional study of unit‐level nursing, patient, and hospital factors versus HAPIs and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Indeed, our study found that units that were high performing in terms of falls used sitters less than low‐performing units, supporting the finding that sitters may not be as effective in reducing falls. Whereas no significant relationship was identified between use of travellers and patient falls, Ferguson et al (2020) found that higher use of travel nurses was associated with a higher rate of hospital‐acquired pressure injuries. Likewise, several studies have found a positive relationship between patient safety outcomes and the amount of overtime hours worked, with higher amounts of overtime leading to higher rates of adverse events, such as falls and health care‐associated infections (He et al, 2016; Son et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, our study found that units that were high performing in terms of falls used sitters less than low‐performing units, supporting the finding that sitters may not be as effective in reducing falls. Whereas no significant relationship was identified between use of travellers and patient falls, Ferguson et al (2020) found that higher use of travel nurses was associated with a higher rate of hospital‐acquired pressure injuries. Likewise, several studies have found a positive relationship between patient safety outcomes and the amount of overtime hours worked, with higher amounts of overtime leading to higher rates of adverse events, such as falls and health care‐associated infections (He et al, 2016; Son et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Annual terminations are those staff who have left the health system. Travellers , also known as contract nurses, are nurses deployed in a temporary position and are not permanent employees (Ferguson et al, 2020). Sitters , also called companions, are staff who provide one‐to‐one observation of high‐risk patients (Greeley et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that rural home health agencies were not able to provide care of comparable quality as urban agencies due to staffing issues. It has been reported that rural agencies rely more on contracted nurses or therapists to provide skilled care, 16,17 and care facilities that have a higher proportion of contracted nurses are more likely to have poor patient outcomes 18 . In addition, providers from home health agencies in rural areas usually spend more time traveling to patient homes for care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that rural agencies rely more on contracted nurses or therapists to provide skilled care, 16,17 and care facilities that have a higher proportion of contracted nurses are more likely to have poor patient outcomes. 18 In addition, providers from home health agencies in rural areas usually spend more time traveling to patient homes for care delivery. These working conditions could result in less efficiencies in care delivery, which ultimately result in poorer patient outcomes, such as higher rates of hospitalization and ED visits.…”
Section: Discussionmentioning
confidence: 99%